International political risk management looking to the future - Moran, Theodore H. 1943-; West, Gerald T. (Gerald Thomas) 1944-; Martin, Geral-Keith (International political risk management, 2005)
The third in a series of volumes based on the MIGA-Georgetown University Symposium in International Political Risk Management, this book offers assessments of needs, trends, and challenges in the international political risk insurance industry. It examines the lessons that can be learned from investment losses, insurance claims, and arbitrations.